Evaluation of Errors on Death Certificates - Atreya, Alok; Acharya, Bina; Yadav, Purushottam Prasad; Menezes, Ritesh G; Nepal, Samata (Journal of Nepal Health Research Council, 2024)
Background: Death certificates provide vital data for disease surveillance and health policy. However, errors are common globally, undermining data reliability. This study analyzed prevalence and types of errors in death certificates at a tertiary hospital in Nepal.Methods: A cross-sectional study reviewed all death certificates issued at Lumbini Medical College, Nepal from April 2020 to April 2022. Certificates were assessed for errors including improper sequencing, absent time intervals, abbreviations, illegible writing, and inaccurate immediate, antecedent, and underlying causes of death as per international guidelines. Errors were classified as major or minor.Results: Of 139 certificates, none were error-free. The most common error was incorrectly or incompletely filling the immediate cause of death (77.7%). Other errors included absent time of death (17.3%), abbreviations (57.6%), illegible writing (22.3%), and omitting the hospital stamp/medical council registration number (8.6%). Based on international criteria, 76.3% had minor errors, 23% had both major and minor errors. Conclusions: This study found a high rate of errors in death certification at a tertiary hospital in Nepal, undermining data accuracy. Regular training and monitoring with feedback are recommended to improve certification practices. Accurate cause-of-death data is vital for healthcare policy and decision-making in Nepal.Keywords: Cause of death; certification; international classification of diseases; major errors and minor errors.